MEMPERKENALKAN SEJARAH PAHLAWAN NASIONAL KH. NOER ALI BAGI PESERTA DIDIK MI/SD DI INDONESIA - Milawati Milawati (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2021)
Heroes have a very big role in the process of the struggle for Indonesian independence. One of the national heroes who fought for Indonesian independence is K.H. Noer Ali. K.H. Noer Ali is a national hero from Bekasi, West Java. The spirit of fighting for Indonesian independence has been in his soul since he was a child. K.H. Noer Ali is a charismatic cleric figure who has a major influence during the Dutch and Japanese colonial times, and is a popular nationalist scholar who is loved by the people. K.H. Noer Ali is also an army cleric with the rank of colonel who is a symbol of the struggle of the people of Bekasi. K.H. Noer Ali contributed a lot to the process of Indonesia's struggle, both in the political, religious, socio-cultural and educational fields. K.H. Noer Ali participates in several Islamic organizations and serves as chairman of the MUI. K.H. Noer Ali is a founder of the Attaqwa Islamic boarding school. As a fighter who has a high spirit of nationalism and homeland command, K.H. Noer Ali participated in educating the nation's children by establishing Islamic boarding schools.